ЎҚУВЧИЛАРНИ ОИЛАВИЙ ҲАЁТГА ТАЙЁРЛАШДА ПСИХОЛОГИК - ИЖТИМОИЙ МУАММОЛАР - Сулетбаева, Э.С. (FAN va JAMIYAT, 2018)
The article deals with the training of learners for family life, psychological features of this problem, skills of family relationship and the rights and responsibility of every member of the family.